2018
DOI: 10.1002/rcs.1909
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional augmented reality surgical navigation with hybrid optical and electromagnetic tracking for distal intramedullary nail interlocking

Abstract: Our results indicate that the AR-guided distal interlocking method is feasible and has many potential applications in clinic after further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 41 publications
1
24
0
1
Order By: Relevance
“…This is in line with previous studies showing that virtual reality methods aimed at improving anatomic visualization help surgeons perform better, particularly during complex tasks such as fracture reduction and fixation . Furthermore, recent studies have shown that augmented reality in combination with opto‐electromagnetic tracking can improve drill hole targeting in distal interlocking procedures …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in line with previous studies showing that virtual reality methods aimed at improving anatomic visualization help surgeons perform better, particularly during complex tasks such as fracture reduction and fixation . Furthermore, recent studies have shown that augmented reality in combination with opto‐electromagnetic tracking can improve drill hole targeting in distal interlocking procedures …”
Section: Discussionsupporting
confidence: 90%
“…[21][22][23][24] Furthermore, recent studies have shown that augmented reality in combination with optoelectromagnetic tracking can improve drill hole targeting in distal interlocking procedures. 25,26 In the current study, the main positive impact of video-augment fluoroscopy was achieved during the C-arm positioning, entry targeting for skin incision (or center punch), and axis control during drilling steps of the procedure. Using VAF resulted in surgeons acquiring fewer fluoroscopic images to complete each step, thus resulting in a reduction in ionizing radiation exposure.…”
Section: Visualizing the Interaction Between Technique And Experiencementioning
confidence: 79%
“…Ma L. et al [50] also investigated locking of IM nails by using an AR navigation system with hybrid optical and electromagnetic tracking. 3D image overlays were provided using an integral videography approach.…”
Section: Instrument / Implant Placementmentioning
confidence: 99%
“…In sensor-based techniques, the location and orientation of the camera are determined through positioning methods and sensors [30][31][32]. On the other hand, in vision-based approaches, computer vision and image-processing techniques are employed to estimate the camera pose [14,[33][34][35]. It is important to mention that this classification does not separate surveyed approaches into disjoint groups because it is possible for an approach to use both techniques.…”
Section: Marker-less Techniquesmentioning
confidence: 99%